Respostas
respondido por:
30
a = 2 b= -6 c=5
delta = (-6)2 -4.2.5
delta = 36 - 40
delta = -4
x= - (-6) + ou - raiz de -4 dividido por 2.2
x = 6 + ou menos 2 dividido 4
x1 = 6+2 = 8 dividido por 4 = 2
x2 = 6-2 = 4 dividido por 4 = 1
delta = (-6)2 -4.2.5
delta = 36 - 40
delta = -4
x= - (-6) + ou - raiz de -4 dividido por 2.2
x = 6 + ou menos 2 dividido 4
x1 = 6+2 = 8 dividido por 4 = 2
x2 = 6-2 = 4 dividido por 4 = 1
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
10 anos atrás
10 anos atrás